Vanadium-containing ordered mesoporous silicas: synthesis, characterization and catalytic activity in the hydroxylation of biphenyl - George, J.; Shylesh, S; Singh, AP (Applied Catalysis A - General, 2005)
A series of vanadium-containing ordered mesoporous MCM-41 materials (V-OMS) have been synthesized by direct hydrothermal (VMCM-41) and grafting (V/MCM-41) methods using hexadecyl trimethyl ammonium bromide (HDTMABr) as the structure-directing agent. The physico-chemical properties of the vanadium-containing materials were characterized in detail by ICP-OES, XRD, Fr-IR, N-2 adsorption-desorption, DRUV-VIS, TPR, XPS and SEM techniques. The redox performances of the vanadium-modified mesoporous materials were tested in the hydroxylation of biphenyl using aqueous H2O2 (30 wt.%) as oxidant. For a better exploitation of the catalytic activity, the reaction parameters are optimized in terms of temperature, solvent, oxidant, etc. A comparison between the catalytic activity values of the vanadium-containing mesoporous materials prepared by the two routes shows that vanadium-substituted (V-MCM-41) materials had increased activity and improved selectivity for mono hydroxyl products in the hydroxylation reaction of biphenyl compared to the V/MCM-41 catalysts. The heterogenity of the catalysts was verified by a series of leaching studies. Both the catalysts enhance the leaching of active vanadia species during the reaction; among them, V/MCM-41 shows the least heterogenity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biphenyl; heterogenity; MCM-41; Mesoporous molecular sieves; Vanadium